Nitrite enhances liver graft protection against cold ischemia reperfusion injury through a NOS independent pathway. Issue 1 (1st January 2017) - Cherif-Sayadi, Amani; Hadj Ayed-Tka, Kaouther; Zaouali, Mohamed Amine; Bejaoui, Mohamed; Hadj-Abdallah, Najet; Bouhlel, Ahlem; Ben Abdennebi, Hassen
ABSTRACT: Introduction : Nitrite has been found to protect liver graft from cold preservation injury. However, the cell signaling pathway involved in this protection remains unclear. Here, we attempt to clarify if the NOS pathway by using the NOS inhibitor, L-NAME (L-N G -Nitroarginine methyl ester). Animals and methods : Rat livers were conserved for 24 h at 4°C in (IGL-1) solution enriched or not with nitrite at 50 nM. In a third group, rats were pretreated with 50 mg/kg of L-NAME before their liver procurement and preservation in IGL-1 supplemented with nitrite (50 nM) and L-NAME (1 mM). After 24 h of cold storage, rat livers were ex-vivo perfused at 37°C during 2 h. Control livers were perfused without cold storage. Results : Nitrite effectively protected the rat liver grafts from the onset of cold I/R injury. L-NAME treatment did not abolish the beneficial effects of nitrite. Liver damage, protein oxidation and lipid peroxidation remained at low levels in both nitrite-treated groups when compared to IGL-1 group. Antioxidant enzyme activities and functional parameters were unchanged after NOS inhibition. Conclusion : Despite NOS inhibition by L-NAME, nitrite can still provide hepatic protection during cold I/R preservation. This suggests that nitrite acts through a NOS-independent pathway.